Antibiotic resistance pattern in urine cultures from community-dwelling women in southern Brazil - a cross-sectional study short communication - Claudia Rejane Mews Peter; Josiane Cristine dos Passos Krause Braga; Lourdes Helena de Araújo Rodrigues; Mauricio Parcio Arrieira; Rafael de Oliveira Arrieira; Maristela Böhlke (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective The increase in antibiotic resistance (AR) is a global phenomenon with regional variation. This survey aims to describe the AR in urine cultures of women from the community in a southern Brazil city. Methods A retrospective cross-sectional single-center study in urine cultures of community dwelling individuals. The main outcome was the AR profile of bacterial isolates from women in outpatient care. Results From 4,011 urine cultures, 524 were positive (91% from women). The most frequently isolated bacteria were Escherichia coli (E. coli) (67.0%) and Klebsiella spp. (19.4%). E. coli presented low resistance to nitrofurantoin (3.7%), moderate to levofloxacin (15.6%), amoxacillin-clavulonate (16.4%) and ciprofloxacin (17.4%), and high to trimethoprim-sulfamethoxazole (26.9%). Conclusions Nitrofurantoin seems to be the best choice for the empirical treatment of low urinary tract infections in women, whereas sulfonamides are no longer an option, since E. coli resistance to this drug is above 20%.